Two hearts beating in a research centers' chest: how scholars in interdisciplinary research settings cope with monodisciplinary deep structures - Hendrik Woiwode; Anna Froese (Studies in Higher Education, 2021)
Interdisciplinary research is a popular mode of knowledge production that becomes intensively promoted by research centers all across the globe. Despite the facilitation of interdisciplinary research, however, scholars working in these centers are `disciplined.' Career promotions, funding decisions and scientific publishing are based on peer-review procedures that tend to favor monodisciplinary research. This paper builds on a qualitative study with scholars in interdisciplinary research centers in Germany and asks how scholars cope with these monodisciplinary demands. After deriving a conceptual framework, the study identifies four coping strategies: disciplinary innovation, strategic compliance, niche-seeking, and field creation. Each of these strategies is characterized by a different degree of openness to knowledge bases of other disciplines and a different degree of proactivity towards monodisciplinary demands from the scientific field. The results illuminate how research agendas become disciplined despite interdisciplinary motivation and organizational support of interdisciplinary research.
Keywords: 330; interdisciplinarity; higher education; governance; management of research centers; coping strategies